Sustainable Valorization of Olive Oil By-products for Food Applications: Mini Review - Almasaudi, Ohoud Hussin; Azhari, Asmahan; Gadallah, Mohamed Gadallah Elsayed (Journal of agricultural, environmental and veterinary sciences, 2025)
The production of olive fruits is a major agricultural and industrial activity with significant economic and vital importance. During the pressing process, about 80% of the material becomes a residue called olive pomace, while only 20% is oil. This ratio varies depending on the type of olive fruit and the extraction method employed, which presents a major challenge for olive presses in terms of draining, disposing of the residue, and protecting the environment. (Medeiros et al., 2016). The chemical analysis of waste from the olive oil industry shows it is high in dietary fiber (54.5%), lipids (11.5%), protein (8.9%), fatty acids, minerals (4%), and antioxidants. This encouraged researchers to utilize it as a food source to fortify food and to benefit from it in the improvement and development of food products as value-added ingredients (Nunes et al., 2019). Some previous studies have also demonstrated the high nutritional value of olive oil industry waste in preventing atherosclerosis, diabetes, obesity, and many other chronic diseases. Additionally, many studies have focused solely on extracting phenols from olive oil industry waste for pharmaceutical and cosmetic uses (Difonzo et al., 2021). The goal of this review is to highlight the positive features of olive pomace, allowing for the introduction of its important components into the development of certain food items. This technology aims to improve the nutritional profile of these meals while also addressing environmental problems related to the disposal of this byproduct.